Parameter evaluation and fully-automated radiosynthesis of [11C]harmine for imaging of MAO-A for clinical trials. (March 2015) - Philippe, C.; Zeilinger, M.; Mitterhauser, M.; Dumanic, M.; Lanzenberger, R.; Hacker, M.; Wadsak, W.
Abstract: The aim of the present study was the evaluation and automation of the radiosynthesis of [ 11 C]harmine for clinical trials. The following parameters have been investigated: amount of base, precursor concentration, solvent, reaction temperature and time. The optimum reaction conditions were determined to be 2–3 mg/mL precursor activated with 1 eq. 5 M NaOH in DMSO, 80 °C reaction temperature and 2 min reaction time. Under these conditions 6.1±1 GBq (51.0±11% based on [ 11 C]CH3 I, corrected for decay) of [ 11 C]harmine ( n =72) were obtained. The specific activity was 101.32±28.2 GBq/µmol (at EOS). All quality control parameters were in accordance with the standards for parenteral human application. Due to its reliability and high yields, this fully-automated synthesis method can be used as routine set-up. Highlights: Preparation of [ 11 C]harmine on a commercially available synthesizer for the routine application. High reliability: only 4 out of 72 failed syntheses; 5% due to technical problems. High yields: 6.1±1 GBq overall yield (EOS). High specific activities: 101.32±28.2 GBq/µmol.